Optimization of Digital-Based Outpatient Administrative Service Systems to Improve Patient Satisfaction in Hospitals in Sidoarjo City - Martianawati; sugiyono; ilmiatus qoyimah (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
The rapid development of digital technology has encouraged hospitals to improve the quality and efficiency of outpatient administrative services. However, many hospitals still experience problems related to long waiting times, inefficient administrative processes, and limited utilization of digital systems, which may affect patient satisfaction. This community service program aimed to optimize the implementation of digital-based outpatient administrative service systems to improve service quality and patient satisfaction in hospitals in Sidoarjo City. The program was conducted using a participatory approach through training, mentoring, and evaluation activities involving hospital administrative staff. The activities included education on online registration systems, electronic medical records, digital queue management, and patient-centered administrative services. Direct mentoring was also provided to assist participants in implementing digital systems in daily administrative activities. Program evaluation was carried out using pre-test and post-test assessments, observations, and patient satisfaction questionnaires. The results showed an improvement in participants’ knowledge and skills regarding digital administrative services. The implementation of digital systems contributed to reduced patient waiting times, improved efficiency in administrative workflows, better accuracy of patient data management, and increased patient satisfaction with outpatient services. Participants also demonstrated greater confidence and readiness in utilizing digital technology within hospital administrative processes. In conclusion, the optimization of digital-based outpatient administrative service systems effectively improved the quality and efficiency of outpatient services in hospitals in Sidoarjo City. Continuous training, infrastructure support, and regular system evaluation are recommended to ensure sustainable implementation and further enhancement of patient satisfaction.